A Comparative Study of Education Recovery Policies in Indonesia and Nigeria - Linh Tran, Thi My; Hoang Doan, Huy (EDUTREND: Journal of Emerging Issues and Trends in Education, 2025)
The COVID-19 pandemic has caused severe disruptions to education systems globally, especially in developing countries. This study compares education recovery policies in Indonesia and Nigeria, focusing on approaches to addressing learning loss among disadvantaged students. Using secondary data analysis and thematic content analysis, the study examined policy documents, reports, and academic literature from 2020 to 2023. The results show that both countries recognize the importance of supporting disadvantaged students, but their strategies differ due to differences in government structures, education investment, and socio-political contexts. Indonesia adopts a centralized approach, emphasizing curriculum reform and school autonomy, as seen in the “Sekolah Penggerak” initiative, while Nigeria relies on community-based initiatives and support from NGOs, such as the Learning Recovery and Accelerated Education Plan. The study highlights the need for context-sensitive policies that prioritize inclusive education and leverage community resources to ensure effective learning recovery.